Features influencing Islamic websites use: a Muslim user perspective - Aliyu, Mansur; Mahmud, Murni; Md Tap, Abu Osman (IIUM Press, 2013)
Muslim scholars and organisations use the Internet through various websites to spread Islam globally. The presence of many websites providing Islamic contents online makes it necessary to examine their Islamic features and the factors that influence Muslims to use Islamic websites. This paper empirically investigates the Islamic features that influence the use of Islamic websites by Muslim users. The identified Islamic factors were grouped under five factors: beliefs, ethics, services, symbols, and values. A survey of 246 Muslim Islamic website users was conducted between November and December 2012 at the International Islamic University Malaysia (IIUM). The study develops and tests a path measurement model to confirm the psychometric properties of the five identified factors. The study found that Islamic features significantly influence Muslims to use Islamic websites. The measurement model and empirical results provide valuable indicators for the direction of future research and also suggest guidelines for developing Islamic websites that will easily influence many Internet users to visit them in order to learn about Islamic teachings and practices. The findings are also of considerable importance as they contribute to the present body of knowledge on Islamic websites’ evaluation and for practice in designing and developing quality Islamic websites.